2019
DOI: 10.1158/1055-9965.epi-18-1122
|View full text |Cite
|
Sign up to set email alerts
|

Potential Markers from Serum-Purified Exosomes for Detecting Oral Squamous Cell Carcinoma Metastasis

Abstract: Background: Blood contains exosomes that are related to tumor cells. Those exosomes can regulate communication between cells and have a great influence on a variety of tumor-associated proceedings through their target cells. Therefore, serum exosomes (SE) were supposed to play a crucial role in cancer development.Methods: This study presented a quantitative proteomics analysis to identify the protein content in SEs including 30 subjects from oral squamous cell carcinoma (OSCC) patients with lymph node metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 46 publications
3
32
0
1
Order By: Relevance
“…Observing that OSCC LN1-1 cells were more aggressive in lymphatic node metastasis than OEC-M1 cells, Wang et al (2019a) used stable isotope amino acid labeling to reveal that higher laminin-332 protein levels in tumor cell-derived exosomes was a major cause for the superior lymphangiogenesis ability of OSCC LN1-1 cells, as laminin-332 promotes lymphatic endothelial cell migration and tube formation. Li et al (2019a) reported that PF4V1, CXCL7, F13A1, and ApoA1 could affect OSCC lymph node metastasis, and the mechanism remains unknown.…”
Section: Exosomes Capsuled Protein In Osccmentioning
confidence: 99%
“…Observing that OSCC LN1-1 cells were more aggressive in lymphatic node metastasis than OEC-M1 cells, Wang et al (2019a) used stable isotope amino acid labeling to reveal that higher laminin-332 protein levels in tumor cell-derived exosomes was a major cause for the superior lymphangiogenesis ability of OSCC LN1-1 cells, as laminin-332 promotes lymphatic endothelial cell migration and tube formation. Li et al (2019a) reported that PF4V1, CXCL7, F13A1, and ApoA1 could affect OSCC lymph node metastasis, and the mechanism remains unknown.…”
Section: Exosomes Capsuled Protein In Osccmentioning
confidence: 99%
“…PF4V1 was evidenced to have statistically significant expressions in cancer tissue samples compared with para-carcinoma tissue samples [21,22]. Additionally, our previous research also found that PF4V1 was not expressed or at a low level in the test samples from OSCC patients with lymph node metastasis compared with OSCC patients with no lymph node metastasis and the healthy population [18]. A close relationship existed between PF4V1 and OSCC.…”
Section: Discussionmentioning
confidence: 71%
“…More and more researches have revealed that PF4V1 regulated cell differentiation, proliferation, and apoptosis [7,16,17]. Our previous study showed that PF4V1 had a close relationship with OSCC [18]. Nevertheless, there has been no study that reports the relationship between PF4V1 and Wnt/β-catenin and EMT pathways in OSCC.…”
Section: Introductionmentioning
confidence: 97%
“…Serum exosomal protein content has been measured and explored as an indicator of locoregional spread. [54] isolated exosomes from serum of subjects, 10 each with OSCC with lymph node metastasis (LNM), OSCC with no LNM (NLNM) and healthy controls (HC). Proteomic comparison using a combination of liquid chromatography-mass spectrometry and mass spectrometry followed by clustering into gene ontology categories.…”
Section: Differential Expression Of Oscc-derived Ev Surface and Cargomentioning
confidence: 99%
“…Of 415 proteins identified, 37 and 28 differentially expressed proteins were identified in OSCC-LNM compared to HC and OSCC-NLNM, respectively. Combined with qPCR-based validation findings from tissue, serum and whole blood samples, they highlighted that serum exosomal proteins, PF4V1, CXCL7, F13A1 and ApoA1 may be related to the OSCC lymph node metastasis [54]. ROC analysis using relative abundances of ApoA1, CXCL7, PF4V1 and F13A1 in serum, serum exosomes and whole blood indicated some potential application as novel predictive circulating biomarkers for OSCC with LNM but are not useful in prognosis.…”
Section: Differential Expression Of Oscc-derived Ev Surface and Cargomentioning
confidence: 99%